Why coding? Why now? From coding to computational thinking through computational mathematics problem based learning (CM-PBL) - Ku, Soh Ting; Talib, Othman; Md. Yunus, Aida Suraya; Zolkepli, Maslina (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
4th Industrial revolution are spreading around the world, embedding the technology into societies. In the digital revolution, high technological tools and resources are regularly being developed. There has been increased attention on learning coding in education field, in order to nurture sufficient number of young generation to fill in 50 percent of jobs opportunity in science, technology, engineering, and mathematics (STEM) which are computing-related. It is increasingly clear that our new generation need to think critically to solve the ill-structured problems, uncertain and complex real world problems. Computational thinking is beneficial in providing automated or semi-automated solutions in problems solving in combination with critical thinking. Therefore, computational thinking is becoming an important implication in science and mathematics as well as in almost every other fields. This fact is reflected in the recent implementation of computer coding in the Malaysia’s school curriculum to nurture 21st century skills among students. Computational thinking is one of the conceptual foundations which required combination of data and ideas to solve problems effectively and efficiently. Computational thinking is essential to computing and information science (i.e., algorithmically, with or without the assistance of computers) to solve problems with solutions that are reusable in different contexts. Promoting different kind of skills and abilities among students is important to solve the complexity problem in real world. Thus, it is a challenging task for many instructors to create a learning environment who lack of feasible resources availability and research-based information to redesign their teaching pedagogies. This conceptual framework is aimed at two goals: (1) development of deep learning, connected computational thinking through the mathematical curriculum instructional model which able to enhance students’ problem solving abilities and (2) implementation of the designed model to assist teacher in education who has practicing difficulty in elementary classrooms after adopting teacher enactment of problem-based curriculum resources. To achieve these goals, computational mathematics problem based learning (CM-PBL) instructional strategy is developed to promote an active learning environment for classroom management involving problem solving. Rather than emphasizing student learning passively through listening, watching, practicing exercises and imitating isolated skills, the CM-PBL learning framework allowing students to simulate and build their own computational models to support their self-learning and understanding of mathematic concepts. It is also highlights ways that students can evolve from technical skills in using technology to soft engineering skills by using coding knowledge.